Pengujian Peran Emas dan Bitcoin Sebagai Aset Safe Haven: Stabilitas vs Spekulasi - Gutama, Zulfikar; Setyahuni, Suhita; Safitri, Maria; Puspitasari, Diana (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2025)
Introduction: This study examines the roles of gold and Bitcoin as safe-haven assets amid global financial uncertainties from 2014 to 2025. While gold is traditionally viewed as a stable asset during market turmoil, Bitcoin's highly volatile and speculative nature challenges its role as a safe-haven. The purpose is to compare the stability and effectiveness of these assets in preserving investment value during crises.Methods: This quantitative research uses 136 monthly return data points of gold and Bitcoin. Analytical methods include independent sample t-tests for comparing average returns and Dynamic Conditional Correlation Generalized Autoregressive Conditional Heteroskedasticity (DCC-GARCH) models to assess volatility and dynamic correlations.Results: Findings reveal gold as a more stable and reliable safe-haven with consistently lower volatility and steadier returns. Bitcoin shows significantly higher volatility and fluctuating dynamic correlations with gold, indicating its speculative behavior. The t-test confirms a significant difference in average returns, while no strong causal relationship exists between the two assets. These results suggest gold is preferable for conservative investors, whereas Bitcoin serves better as a high-risk diversification instrument. Keywords: Bitcoin, Gold, DCC-GARCH, Safe Haven Asset, Investment Asset